Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T19:15:20+01:00
C) 2x - 2 + 3x + 3 = 26
5x + 1 = 26
5x = 26 - 1
5x = 25/:5
x = 5
d) 12 - 4x +9 = 14 + 7x + 29
21 - 4x = 7x + 43
-4x - 7x = 43 - 21
-11x = 22/:(-11)
x = -2
e) 2x - 6 + 3x -12 + 4x - 20 = 0
9x - 38 = 0
9x = 38/:9
x = 4 i 2/9
2010-03-17T19:15:33+01:00
C) 2(x-1)+3(x+1)=26
2x-2+3x+3=26
2x+3x=26+2-3
5x=25
x=25:5
x=5

d) 4(3-x)+9=7(2+x)+29
12-4x+9=14+7x+29
4x-7x=14+29-12-9
-3x=22
x=22:(-3)
x=-7,3

e) 2(x-3)+3(x-4)+4(x-5)=0
2x-6+3x-12+4x-20=0
2x+3x+4x=0+6+12+20
9x=38
x=38:9
x=4,(2)
2010-03-17T19:19:23+01:00
Chciałam pomóc, ale widzę że mnie wyprzedzili ;))